2020
DOI: 10.1074/jbc.ra120.014080
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the RNA-binding protein Rbm15 disrupts liver maturation in zebrafish

Abstract: Liver organogenesis begins with hepatic precursors in the foregut endoderm, followed by hepatoblast specification, differentiation, outgrowth, and maturation for the formation of functional hepatocytes. Although several signaling pathways and critical factors that regulate liver specification, differentiation, and proliferation have been identified, little is known about how liver maturation is regulated. Here, we used a screen for mutations affecting liver development in zebrafish and identified a cq96 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Expression analysis of uox in zebrafish using whole mount in situ hybridization (WMISH) showed expression at 2 dpf in the developing liver, with weaker diffuse expression in the head and along the horizontal myoseptum ( Figure 2 A). By 4 dpf, this expression pattern remained, with strong expression in the liver and weaker expression in extrahepatic tissues ( Figure 2 A), consistent with a previous study [ 38 ]. To generate the uox knockout line, we used CRISPR/Cas9 gene editing to target exon 2 and create a premature termination codon early in the transcript ( Figure 2 B).…”
Section: Resultssupporting
confidence: 91%
“…Expression analysis of uox in zebrafish using whole mount in situ hybridization (WMISH) showed expression at 2 dpf in the developing liver, with weaker diffuse expression in the head and along the horizontal myoseptum ( Figure 2 A). By 4 dpf, this expression pattern remained, with strong expression in the liver and weaker expression in extrahepatic tissues ( Figure 2 A), consistent with a previous study [ 38 ]. To generate the uox knockout line, we used CRISPR/Cas9 gene editing to target exon 2 and create a premature termination codon early in the transcript ( Figure 2 B).…”
Section: Resultssupporting
confidence: 91%
“…RBM15 binds to RNA to regulate post-transcriptional modifications (106) such as alternative RNA splicing, polyadenylation, and protein translation. RBM15 is not only essential for megakaryocyte differentiation (107), but also indispensable for liver development (74). Hu et al (74) found RBM15 was expressed in the liver during its differentiation, and depletion of RBM15 specifically suppressed hepatic maturation and caused liver failure but did not affect hepatocyte proliferation and apoptosis.…”
Section: Rbm15mentioning
confidence: 99%
“…RBM15 is not only essential for megakaryocyte differentiation (107), but also indispensable for liver development (74). Hu et al (74) found RBM15 was expressed in the liver during its differentiation, and depletion of RBM15 specifically suppressed hepatic maturation and caused liver failure but did not affect hepatocyte proliferation and apoptosis. More studies are needed to understand the role of RBM15 in hepatic maturation and liver diseases.…”
Section: Rbm15mentioning
confidence: 99%
“…This indicates that RBM15-mediated m 6 A RNA methylation may be implicated in the immune infiltration of OS. RBM15 is a critical methyltransferase that regulates the fate of cellular mRNA molecules by catalyzing the formation of m 6 A in mRNA; it has been previously uncovered in cortical development, 22 liver maturation, 23 and Xist-mediated X chromosome inactivation. 24,25 It is worth noting that we downloaded mutation data from TCGA for mutant processing of SARC and found that RBM15 is mainly mutated in a RNA recognition motif (RRM) with a somatic mutation rate of only 0.84%.…”
Section: Discussionmentioning
confidence: 99%